Response surface method and its application in system reliability analysis of bridges - Guanghui, Li; Chenyu, Liu; Laounifuliao, Tuo; Onoufriou, Toula (My University, 2004)
A new method aiming to incorporate the response surface method (RSM) into the computation of the system reliability for composite bridges is proposed in this paper. The nonlinear finite element analysis program is first used to analyze the ultimate capacity of bridge structure on the basis of experimental design, and then, the response surface method is applied to obtain the response surface of the system capacity of the bridge. At last, system reliability results are got with the aid of the universal probability analysis program. The validity of the proposed method has been examined through the computation of the system reliability of a single-span composite bridge.
Keywords: bridges